Species persistence in northerly glacial refugia of Europe: a matter of chance or biogeographical traits? - Bhagwat, SA; Willis, K (2008)
Aim: The southern European peninsulas (Iberian, Italian and Balkan) are considered to have been refugia for many European species of plants and animals during the climatic extremes of the Pleistocene ice ages. A number of recent studies (fossil and genetic), however, have provided evidence for full-glacial survival of some species beyond these peninsulas. Here we explore the biogeographical traits of these species, and ask whether they possessed certain characteristics that enabled them to persist in more northerly refugia. Location: Europe. Methods: Fossil and genetic evidence for refugial localities of species that survived in Europe during the last full-glacial was obtained from the literature (totalling 90 species: 34 woody plants and 56 vertebrates). Forty-seven of these species (23 woody plants and 24 vertebrates) had fossil evidence, whereas the remaining 43 species (11 woody plants and 32 vertebrates) had only genetic evidence. All species were scored according to their present geographical distribution, habitat preference and life-history traits. The species were classified on the basis of these traits using hierarchical cluster analysis. Analysis of similarities was used to examine differences in vertebrate and woody plant species groups that survived only in southerly refugia and those that also persisted in more northerly locations. Non-metric multi-dimensional scaling was used to examine patterns observed between and within groups. Results: Results from our analysis of species with fossil and genetic evidence for survival in refugia reveal that species that survived only in southerly refugia were large-seeded trees or thermophilous vertebrates. In contrast, species that had a full-glacial distribution, including more northerly locations, were wind-dispersed, habitat-generalist trees with the ability to reproduce vegetatively, and habitat-generalist mammals with present-day northerly distributions. Main conclusions: Analysis of the geographical distribution, habitat preference and life-history traits of the species studied suggests that underlying biogeographical traits may have determined their response to Pleistocene glaciation. The traits most commonly found in present populations with a northerly distribution in Europe enabled the same species to exist much farther north than the southern European peninsulas during the full-glacial. It is possible that many of these species are now in restricted populations, within the 'warm-stage' refugia of the current interglacial. The northerly full-glacial survival of a number of woody plants and vertebrate species has significant implications for understanding migration rates of these species in response to climate change. It also has important implications for understanding current patterns of genetic diversity of European species. We suggest that both fossil and genetic evidence should be used to identify and prioritize for conservation of refugial localities in southern and northern Europe. © 2008 The Authors.